2014
DOI: 10.1093/ntr/ntu010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine Deprivation and Replacement on BOLD-fMRI Response to Smoking Cues as a Function of DRD4 VNTR Genotype

Abstract: introduction: Reactivity to smoking cues is an important factor in the motivation to smoke and has been associated with the dopamine receptor 4 variable number tandem repeat (DRD4 exon III VNTR) polymorphism. However, little is known about the associated neural mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Acute NRT administration following overnight abstinence was associated with greater smoking cue‐elicited striatal and amygdalar activation in a sample of non‐treatment‐seeking smokers (Xu et al . ); yet, discrepancies in treatment‐seeking status and duration of abstinence complicate the integration of these NRT results with those previously described.…”
Section: Pharmacological Treatment Effects On Neural Substrates Of Cumentioning
confidence: 78%
“…Acute NRT administration following overnight abstinence was associated with greater smoking cue‐elicited striatal and amygdalar activation in a sample of non‐treatment‐seeking smokers (Xu et al . ); yet, discrepancies in treatment‐seeking status and duration of abstinence complicate the integration of these NRT results with those previously described.…”
Section: Pharmacological Treatment Effects On Neural Substrates Of Cumentioning
confidence: 78%
“…For example, Bruijnzeel et al (2014) observed greater brain activation to nicotine administration (compared to saline injection) in rats in brain areas commonly associated with reward processing (e.g., nucleus accumbens, amygdala, and insula) and behavioral planning/imagining (e.g., motor and somatosensory cortices). In abstinent cigarette smokers, Xu et al (2014) reported that wearing a nicotine patch resulted in greater brain activation to cigarette videos in the bilateral ventral striatum and left amygdala when compared with neutral videos. Notably, the placebo patch did not have such an effect, suggesting that nicotine administration was responsible for these cue-related neural responses.…”
Section: Discussionmentioning
confidence: 99%
“…Phenomenologically, this may be related to increased expectations of use, particularly if they were not fully sated by the drug administration (e.g., see Xu et al, 2014). To explore this option more fully in our participants, we conducted post-hoc analyses to assess the degree of fulfilment our participants felt from the vaping protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who carry at least one “long” allele ( DRD4-L ) are less common in the general population. Analysis of cell lines indicate that DRD4-L is associated with reduced ligand binding and reduced cyclic adenosine monophosphate formation when dopamine is receptor-bound (Asghari et al, 1995), suggesting reduced dopaminergic tone in the mesocorticolimbic pathway (Brody et al, 2006; Rivera et al, 2002; Xu et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The presence of the DRD4-L allele in smokers has also been associated with enhanced reactivity to smoking cues (Hutchison et al, 2002; Munafo and Johnstone, 2008). Furthermore, DRD4-L smokers show greater activation of right superior frontal gyrus and right insula in response to smoking cues (McClernon et al, 2007), as well as differences in amygdala activation (Xu et al, 2014) using functional magnetic resonance imaging (fMRI).…”
Section: Introductionmentioning
confidence: 99%